Efektivitas Dakwah Hadis dalam Media Sosial: Analisis atas Teori Framing Robert N. Entman - Perdana Putra Pangestu (Jurnal Dakwah dan Komunikasi, 2021)
Hadis preaching is now meeting new challenges in its succession of implementation, one of which is its touch with courage-based social media. Apart from optimizing the propagation material that is disseminated, it has also become an interesting topic in discussions of the development of modern dakwah. In this case, content framing (framing) is deemed appropriate to package the dakwah content offered to the people in order to have authority on social media. However, the question that can be offered is how can the theoretical application of the framing concept work on da'wah content on social media? Departing from this formula, the author will elaborate the dakwah paradigm through content from several accounts on Instagram, based on the hadith as the preaching material. The author provides segmentation of the @hadispedia and @pusatkajianhadis accounts as research objects using the theoretical synergy of Robert N. Entman's framing. This research is built on qualitative methods that are oriented towards the context of reality and data analysis of digital literature. The author will examine the focus of the problem with a descriptive-explorative orientation in order to obtain an optimal and comprehensive understanding. The argument from this research is that the concept of framing actualized on the preaching of hadith content, especially on @hadispedia and @pusatkajianhadis accounts, can increase the effectiveness of the implementation of da'wah on social media.